2020
DOI: 10.1111/jfbc.13539
|View full text |Cite
|
Sign up to set email alerts
|

The IgE/IgG binding capacity and structural changes of Alaska Pollock parvalbumin glycated with different reducing sugars

Abstract: Parvalbumin (PV) is one of the major allergens in fish. The aim of our present work was to research the influence mechanism of glycation with different reducing sugars (glucose, fructose, ribose, lactose, and galactose) on the immunoglobulin E (IgE) and immunoglobulin G (IgG) binding capacity and structure changes of PV in Alaska Pollock. PV glycated with glucose or fructose (PV-Glu/ PV-Fru) exhibited the higher IgE/IgG binding capacities than that of ribose, galactose, or lactose. During glycation, the lysine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Zhao et al [ 95 ] found that MR with glucose can reduce the IgE reactivity of recombinant silver carp parvalbumin, because glycation sites overlapped with K88, K97, and K108 in epitopes. Zhang et al [ 96 ] glycated Alaska Pollock parvalbumin with glucose, fructose, ribose, lactose, and galactose, while only the reaction with ribose/galactose reduced its IgE binding capacity. Yang et al [ 97 ] processed parvalbumin by boiling, ultrasonic treatment, ultraviolet treatment, pressure treatment, and MR.…”
Section: Maillard Reaction and Allergenicity Of Foodsmentioning
confidence: 99%
“…Zhao et al [ 95 ] found that MR with glucose can reduce the IgE reactivity of recombinant silver carp parvalbumin, because glycation sites overlapped with K88, K97, and K108 in epitopes. Zhang et al [ 96 ] glycated Alaska Pollock parvalbumin with glucose, fructose, ribose, lactose, and galactose, while only the reaction with ribose/galactose reduced its IgE binding capacity. Yang et al [ 97 ] processed parvalbumin by boiling, ultrasonic treatment, ultraviolet treatment, pressure treatment, and MR.…”
Section: Maillard Reaction and Allergenicity Of Foodsmentioning
confidence: 99%
“…Also, a large number of hydrophobic groups had been exposed due to proteins unfolding (18). The increase of surface hydrophobicity resulted in the harder binding of IgG or IgE with protein (31). The partial unfolding of OVA induced by phosphorylation may result in the damage of conformational IgG and IgE epitopes and lead to the reduction of IgG and IgE-binding of OVA.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, shrimp TM solution was adjusted to 10 mg mL −1 by phosphate buffer solution (PBS, pH 7.4). According to the previous studies, ribose solutions were prepared at a concentration of 5, 50, 250, 500, 1000, 2000 and 4000 mmol L −1 using the same phosphate buffer during the experiment, respectively (Fu et al ., 2019; Zhang et al ., 2021). The TM and ribose solutions were mixed in equal volumes for 24 h at 60 ℃.…”
Section: Methodsmentioning
confidence: 99%